Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1974
DOI: 10.1111/j.1748-1716.1974.tb05776.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Efficiency and Storage of Elastic Energy in Human Muscles during Exercise

Abstract: ASMUSSEN, E. and F. BONDE-PETERSEN. Apparent efficiency and storage of elastic energy in human muscles during exercise. Acta physiol. scand. 1974. 92. 537-545.3 subjects ran on the treadmill (10 km/h) against varying horizontal impeding forces. One subject was further studied during the same kind of walking and bicycling on the treadmill, and during work consisting in lowering and lifting the body by flexing and extending the legs from a standing or sitting position a t varying frequencies, with or without reb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(85 citation statements)
references
References 15 publications
6
77
2
Order By: Relevance
“…In the present study the mean cycling D efficiency was 25%. Results from previous studies (Asmussen and Bonde-Petersen 1974;Suzuki 1979;Coyle et al 1992;Bijker et al 2001) have also shown that the D efficiency of cycling is indeed less than the efficiency of concentric exercise.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the present study the mean cycling D efficiency was 25%. Results from previous studies (Asmussen and Bonde-Petersen 1974;Suzuki 1979;Coyle et al 1992;Bijker et al 2001) have also shown that the D efficiency of cycling is indeed less than the efficiency of concentric exercise.…”
Section: Discussionmentioning
confidence: 83%
“…As a result, the gross efficiency during running can be much greater than the muscle efficiency (van Ingen Schenau et al 1997;Ettema 2001). Previous studies suggested that during running up inclines storage and re-use of elastic energy also takes place, which could explain the large D efficiencies obtained during running (Lloyd and Zacks 1972;Asmussen and Bonde-Petersen 1974). According to van Ingen Schenau (1984), however, during running up inclines, work produced by the muscles to overcome the external force is lost and can therefore not be stored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of methods described in the previous studies, subjects performed horizontal load walking at 1.11 m/s (4 km/h) [2,5]. Horizontal loads were imposed using weights in a small basket that was connected to a wire, which was passed through a pulley and attached to a band around a subject's waist (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Lloyd and Zacks [1] estimated the mechanical efficiency (Apparent Efficiency, AE) during treadmill running on the basis of the rate of increasing energy expenditure for increment of work rate (load × velocity). Asmussen and Bonde-Petersen [2] also reported about the AE of walking and running using a similar technique according to Lloyd and Zacks [1]. Bijker et al [3] compared the delta efficiency of running with that of a bicycle ergometer exercise.…”
Section: Introductionmentioning
confidence: 99%